ACUTE ORAL TOXICITY STUDIES WITH K-OTHRINE (A SYNTHETIC PYRETHROID INSECTICIDE) IN SWISS ALBINO MICE - CHAWLA, RAJNI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Toxicity of K-othrine against Swiss albino mice was evaluated by oral force feeding. The test species revealed high susceptibility to the toxicant as indicated by steep nature of the dosage mortality regression line duly substantiated by Finneys Probit analysis of data to give regression equation (-7,704 ± 5.97X). Median lethal dose of LD50 and LD90 for combined sexes was found to be LD50= 13.43/(10.64 - 16.90) mg/kg b, wt and LD 90= 21.93/(17.38 - 27.67) mg/kg b, wt. Gross clinical symptoms observed were paralysis, extensive tremors, salivation, vomiting, ataxia and a hunch on the back was developed within 1 hour or 2 hours of pesticide intoxication in some of the mice.